Deep Brain Stimulation for Alzheimer’s Disease: A Review of a Potential Treatment in Neurosurgery - Husodo, Kharisma Ridho; Fa'izah, Chintya Nur (Jambura Medical and Health Science Journal, 2024)
Background: Alzheimer’s disease (AD) is still a disease with abundant enigma. Moreover, the prevalence of AD increases every year by about 10 million new cases. This disease is well known for its degenerative feature with age being the most influencing factor. Pathophysiologically, the deposition of beta-amyloid and tau proteins is the culprit for disrupting the neural connections in the brains of AD patients. Some studies have stated that drug medications are not effective in treating AD patients.Content: Currently, there is no drug to cure the disease. In conditions in which drugs fail to take effect, there is a therapy called deep brain stimulation (DBS), which allows the brain to be stimulated electrically using electrodes that are implanted into certain brain areas as targets. In AD patients, the nucleus basalis of meynert (NBM) and fornix are frequently selected as targets in DBS. This intervention is performed surgically by the neurosurgeon. Several potential mechanisms of this treatment include controlling connections among neurons, decreasing beta-amyloid and tau protein levels, and inhibiting the inflammation process in the brain.Conclusion: DBS can improve AD patients, both clinically and molecularly. Despite the promising effects of DBS, this treatment has limitations, so it cannot be applied to every patient with AD.